Pengaruh Good Corporate Governance terhadap Kinerja Keuangan Pada Perusahaan Transportasi dan Logistik - Radhiyatul Balqis; Muslim Ansori (Politeknik Negeri Batam, 2025)
The effect of good corporate governance on financial performance is the focus of this study. by involving control variables, namely Company Size and covid-19 dummy variables. The study’s population consist of Transportation and Logistics companies listed on the Indonesia Stock Exchange for the period 2021-2023, there are 37 companies. 23 companis ware sampled in this study based on criteria. This research methodology uses multiple linear regression analysis. This data processing utilizes the SPSS Ver26 application. Considering the findings of the analysis, this research indicates that managerial ownership, institutional ownership and audit committee have a positive effect on financial performance. but the independent board of commissioners and the audit committee have no effect on financial performance.